EFFECTIVENESS OF DIFFERENTIATED LEARNING PROCESS ON SOCIOMATHEMATICAL SKILLS OF GRADE VIII - Febrianti Br Sitanggang; Simon M Panjaitan; Lolyta Damora Simbolon; Dame Ifa Sihombing; Lena R. Pangaribuan (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This study aims to determine the effectiveness of differentiated learning processes on the social mathematical skills of class VIII students at SMP Negeri 18 Medan. This type of research is quantitative descriptive research with the research population being all class VIII students at SMP Negeri 18 Medan. With a simple random sampling technique, a sample of class VIII-10 was obtained with 32 students. The instruments used were questionnaires and observations that had been tested for prerequisites in advance. After the differentiated learning process treatment was carried out, the results of the calculation of the learning quality questionnaire sheet reached an effectiveness category of 56% (moderate), the results of the calculation of the social skills questionnaire sheet reached an effectiveness category of 66% (moderate), the results of the calculation of the observation sheet for the suitability of the learning level to teacher activities obtained an average of 3.476 (good), the results of the calculation of the observation sheet on student activities obtained an average of 3.039 (good), the results of the calculation of the time allocation observation sheet obtained an average of 4 (good). Based on the quality of learning, the suitability of the learning level and time allocation, differentiated learning is effective for the social mathematical skills of class VIII students at SMP Negeri 18 Medan.